Transitional Cell Carcinoma of the Kidney Graft: An Extremely Uncommon Presentation of Tumor in Renal Transplant Recipients - Vital Hevia; Victoria Gómez; Sara Álvarez; Víctor Díez Nicolás; Carmen Gómez del Cañizo; Andrea Orosa; Cristina Galeano Álvarez; F. J. Burgos Revilla (Case Reports in Transplantation)
Purpose. Transitional cell carcinoma (TCC) affecting the graft after renal transplantation is a very infrequent way of presentation of this tumor. Our aim is to present our single institution experience with 2 cases, as well as to perform a review of the literature about this tumor after the transplant. Materials and Methods. TCC of the graft developed in 2 of 1365 patients from 1977 to 2010, both cases in women. Data were analyzed for incidence, clinical presentation, treatment, and outcomes. Results. Both cases occurred in 2 mid-age women and resulted to be high grade and locally advanced TCCs, representing an incidence of 0,14% (2/1365). Clinical presentation was urinary obstruction for the first case and incidental ultrasound finding for the second. Preoperative staging was made with CT, cytology, pyelography, ureterorenoscopy, and biopsy. Treatment performed was nephroureterectomy of the graft with bladder cuff and regional lymphadenectomy. Pathological examination showed in both cases a locally advanced and high grade urothelial carcinoma of the pelvis allograft. After 24 and 14 months of followup, both patients are disease free. Conclusions. TCC of the kidney graft is an infrequent tumor that has only been reported in a few cases in the literature. It usually appears at a lower age, more often locally advanced, and with poor differentiation. A multidisciplinary approach to treatment should be required in these cases.